Pengaruh Struktur Modal, Likuiditas, Profitabilitas Dan Ukuran Perusahaan Terhadap Manajemen Laba Riil Dengan Komisaris Independen Sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Arini, Novia Dewi; , Dr. Triyono, SE, M.Si (2017)
The aim of this research was to analyzedthe effect of capital structure as measured by leverage, liquidity, profitability and the firm sizeon real earnings management with independent board as variable moderation. Population of this research was all of manufacturing firms listed on Indonesian Stock Exchange (BEI) in 2011-2015. The sampling method used purposive sampling methodand obtained as many as 301 companies. Data analysis method used multiple linier regression method.The result showed that the firm size and leverage haveeffect on real earnings management while the liquidity and profitability have no effect on real earnings management. Leverage and liquidity that was moderated by independent boardhave no effect on real earnings management while the profitability and firm sizethat was moderated by independent board have effect on real earnings management